(U-TH)/HE GEOCHRONOLOGY OF SINGLE ZIRCON GRAINS OF KNOWN TERTIARY ERUPTION AGE - Tagami T.; Farley K.A.; Stockli D.F. (My University, 2003)
We performed a systematic study of (U-Th)/He ages of volcanic zircons of known eruption age to establish a reliable protocol for zircon He dating and to validate the resulting ages. Using laser He extraction and dissolution by lithium borate flux melting we analyzed many aliquots of single zircon grains separated from four rapidly cooled rocks: Fish Canyon Tuff (accepted age 27.8+/-0.7 Ma), Buluk Tuff (16.3+/-0.2 Ma), Tardree Rhyolite (58.4+/-0.7 Ma) and Utaosa Rhyolite (2.52+/-0.02 Ma). He ages of Fish Canyon Tuff, Buluk Tuff and Utaosa Rhyolite zircons are in good agreement with their reference ages: mean α emission-corrected ages were 28.6+/-1.4 (1σ), 16.1+/-0.8 and 2.61+/-0.18 Ma, respectively. However, the zircon He ages of Tardree Rhyolite are irreproducible and consistently too old, with a mean He age of 78.8+/-7.0 Ma. Spontaneous fission track densities of Tardree Rhyolite zircons indicate that about 80% of these zircons are strongly zoned in U, with high track density (i.e., high U content) in the core and low density on the rim. This causes an overestimation of the α ejection correction that likely explains the erratic and excessively high He ages from these zircons. Assessment of the degree and style of U zonation within a zircon population is thus prudent before application of the (U-Th)/He method. Step-heating experiments indicate that for most zircons He extraction is >99% complete after ~1 h at 1300°C. However, for as yet unknown reasons occasional grains seem to retain substantial amounts of He under these conditions.
Keywords: ZIRCON; HELIUM; GEOCHRONOLOGY; STANDARD; LASER HEATING